Estimating directional data from network topology for improving tracking performance - Tomic, Slavisa (2019)
UID/MULTI/04111/0213 UID/MULTI/04111/0216 PCIF/SSI/0102/2017 UID/EEA/50008/2019 PES3N POCI-01-0145-FEDER-030629 Grant IF/00325/2015